Effect of flow on the corrosion behaviour of API 5L X80 steel in supercritical CO2 systems - Sá, Jonas da Silva de (2022)
In this work,the effect of water-saturated supercritical CO2 and CO2-saturated water flow rate on the corrosion behaviour of API 5L X80 steel at a temperature of 35°C and pressure of 80 bar was investigated. Tests were carried out with the samples attached to a rotating shaft inside an autoclave. Results indicate that increasing the CO2-saturated water flow rate increased the corrosion rate in the absence of a corrosion product film, but later favoured the precipitation of a dense and more protective crystalline carbonate layer. Besides that, the presence of Ca2+ in the brine favoured the precipitation of a mixed iron-calcium carbonate (FexCa1˘xCO3) film with increasingly calcium molar mass that offered better protectiveness to the carbon steel when compared to the pure iron carbonate (FeCO3). On the other hand, in water-saturated supercritical carbon dioxide systems, increasing the flow rate had no significant influence on the general/localized corrosion rate under the various dynamic conditions considered, because the size of the condensed water droplets, were much smaller than the calculated critical droplet size needed to be displaced by the supercritical CO2 flow.